KINERJA KOORDINASI SIMPANG CEBONGAN DAN SIMPANG TAMAN RINGIN CEBONGAN BERDASARKAN PKJI 2023 - Ad Zulfa Geofani Firdaus (Jurnal Teknik Sipil, 2024)
Simpang 4 Cebongan and Simpang 3 Taman Ringin Cebongan are intersections that have a shelf size of 230 m and are located in a commercial environment that is dense with motor vehicles, so that the queue at one of the intersections can interfere with the performance of adjacent intersections. The performance analysis of existing conditions and intersection coordination is based on the 2023 Indonesia’s Road Capacity Guidelines (PKJI), while the microsimulation uses VISSIM PTV software. The results of the analysis show that based on PKJI 2023, the saturation degree values in the existing conditions of Simpang 4 Cebongan and Simpang 3 Taman Ringin Cebongan are 0.8 and 0.52. The solution to reduce the queue length on Jalan Kebon Agung that connects the two intersections is to coordinate the two intersections with a cycle time of 100 seconds at both intersections with 4 phases at Simpang 4 Cebongan and 3 phases at Simpang 3 Taman Ringin Cebongan, so that the bandwidth value from West to East is 29 seconds with a bandwidth efficiency of 29% and from East to West is 19 seconds with a bandwidth efficiency of 19%. The length of the intersection queue with the application of this condition decreased from 198.32 m to 179.93 m.